2017
DOI: 10.1186/s12943-017-0648-1
|View full text |Cite
|
Sign up to set email alerts
|

ROS signaling under metabolic stress: cross-talk between AMPK and AKT pathway

Abstract: Cancer cells are frequently confronted with metabolic stress in tumor microenvironments due to their rapid growth and limited nutrient supply. Metabolic stress induces cell death through ROS-induced apoptosis. However, cancer cells can adapt to it by altering the metabolic pathways. AMPK and AKT are two primary effectors in response to metabolic stress: AMPK acts as an energy-sensing factor which rewires metabolism and maintains redox balance. AKT broadly promotes energy production in the nutrient abundance mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
379
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 511 publications
(393 citation statements)
references
References 123 publications
(145 reference statements)
11
379
0
3
Order By: Relevance
“…Recent reports have suggested that high glucose‐induced AKT signaling increases ROS levels by activating mTOR signaling, which induces glucose metabolism and protein synthesis, and by inhibiting FOXO signaling, which induces antioxidant gene transcription (Nogueira et al, 2008; Sheu et al, 2004). Consequently, AKT activation increases metabolic stress and ROS, resulting in a positive feedback loop that promotes cellular senescence (Dolado & Nebreda, 2008; Zhao et al, 2017). To investigate the activation of AKT in WT and KO MEF cells, we treated MEF cells with various concentrations of glucose or insulin, a peptide hormone that regulates glucose uptake, as a metabolic stress inducer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have suggested that high glucose‐induced AKT signaling increases ROS levels by activating mTOR signaling, which induces glucose metabolism and protein synthesis, and by inhibiting FOXO signaling, which induces antioxidant gene transcription (Nogueira et al, 2008; Sheu et al, 2004). Consequently, AKT activation increases metabolic stress and ROS, resulting in a positive feedback loop that promotes cellular senescence (Dolado & Nebreda, 2008; Zhao et al, 2017). To investigate the activation of AKT in WT and KO MEF cells, we treated MEF cells with various concentrations of glucose or insulin, a peptide hormone that regulates glucose uptake, as a metabolic stress inducer.…”
Section: Resultsmentioning
confidence: 99%
“…KO mice exhibited greater AKT signaling, insulin sensitivity, and glycolysis in oxidative tissues than WT mice, which was associated with impaired mitochondrial fuel oxidation and the accumulation of oxidized PTEN (Hui et al, 2008). Intracellular ROS induce AKT activation, which in turn induces premature senescence by increasing ROS levels via inhibition of the transcriptional activity of the FOXO family and by activating mTOR pathways (Dolado & Nebreda, 2008; Johnson et al, 2013; Sheu et al, 2004; Zhao et al, 2017). Other groups also reported the function of AKT in aging.…”
Section: Discussionmentioning
confidence: 99%
“…Originally thought to be merely damaging byproducts of cell metabolism, ROS have recently been found to function as a signaling molecule that can activate cascades of signal transducers to address oxidative stress [Radak et al, 2013;Bigarella et al, 2014;Navarroyepes et al, 2014;Zhao et al, 2017]. Additionally, ROS may also oxidize or modify macromolecules, such as proteins, DNA, and lipids.…”
Section: Discussionmentioning
confidence: 99%
“…NADPH, the predominant reducing agent in organisms, participates in a number of metabolic reactions. GSH is dehydrogenated to form glutathione disulfide, which is in turn reduced to GSH by glutathione reductase in the presence of NADPH (43). Given the functions of GSH, the synthesis of NADPH is important in resistance to peroxidation-induced damage during ferroptosis.…”
Section: Metabolism and Ferroptosismentioning
confidence: 99%